2014
DOI: 10.1163/18754112-1802003
|View full text |Cite
|
Sign up to set email alerts
|

Where Do Peacekeepers Go When They Go?

Abstract: Recent developments in the availability of spatial data and the growing trend of spatial analysis in political science has given scholars the ability to account for local-level factors in the study of political violence and conflict management. In this paper, the authors contribute to this growing body of literature by employing geo-coded data to empirically explore a question central to the study of peacekeeping – when peacekeepers are authorized to enter a conflict, where do they go? In other words, what typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…Our control variable for international borders is the most substantive and consistent of our control variables followed closely by road networks. These findings are consistent with the previous analysis on just the DRC in Townsen and Reeder (). Our control for population density is significant in Angola, Ivory Coast, and Sierra Leone but never so in the DRC.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Our control variable for international borders is the most substantive and consistent of our control variables followed closely by road networks. These findings are consistent with the previous analysis on just the DRC in Townsen and Reeder (). Our control for population density is significant in Angola, Ivory Coast, and Sierra Leone but never so in the DRC.…”
Section: Resultssupporting
confidence: 93%
“…Although the prior literature on the determinants of PKO location has amassed a considerable amount of evidence regarding the various state‐ and international‐level factors that impact the types of countries PKOs find themselves in, there is almost no work that examines where PKOs go once they are deployed to a civil war‐torn country . The only exceptions to this trend are found in the work of Costalli () and Townsen and Reeder (). Using disaggregated spatial data on both civil war battles and peacekeeping operations, Costalli () finds that, although PKOs went to the most violent regions during the Bosnian civil war, they were largely unsuccessful in mitigating civil violence.…”
Section: Where To Keep the Peace?mentioning
confidence: 91%
See 2 more Smart Citations
“…The logic underlying this position is relatively straightforward: if peacekeepers are not located in close proximity to violence, then they are unlikely to have an opportunity to influence the behaviour of local conflict actors. The most effective operations should therefore have the majority of their personnel located near potential 'hot spots' around the country, rather than deployed according to a 'convenience' logic that might see them stationed far away from the sources of violence (Ruggeri, Gizelis and Dorussen 2011;Townsen and Reeder 2014;Powers, Reeder and Townsen 2015;Ruggeri, Dorussen, Gizelis 2018). Although not all studies agree that peacekeepers are effective when co-located with violence (Costalli 2014), the majority have found that geographic location is an essential component of success.…”
Section: Operational Effectivenessmentioning
confidence: 99%